124 Intraventricular Hemorrhage Clearance Markers in Human Neonatal Cerebrospinal Fluid: Predictors of Hydrocephalus and Outcome. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Buddhala, Chandana; Paturu, Mounica; Morales, Diego; Smyser, Christopher; Limbrick, David D; Mahaney, Kelly B; Strahle, Jennifer
Abstract: INTRODUCTION: Infants with intraventricular hemorrhage (IVH) are at risk for posthemorrhagic hydrocephalus (PHH) and poor outcomes. Iron has been implicated in cell death, brain injury, PHH, and poor outcomes in animal models. We hypothesized differences in endogenous iron clearance markers or blood breakdown pathways in IVH influence development of PHH and neurodevelopmental outcomes. METHODS: Cerebrospinal fluid (CSF) lumbar puncture (LP) samples were analyzed in premature infants with no IVH (n = 11), grades I-II IVH (n = 4), grades III-IV IVH (n = 8), and PHH (n = 11). Serial CSF ventricular taps (VT) in a subset of PHH neonates (n = 8) were analyzed separately. Hemoglobin (Hb), transferrin, hemopexin, ceruloplasmin, ferritin, haptoglobin, nonprotein-bound iron, total bilirubin, and hepcidin were analyzed using commercially available ELISAs. For neonates with VT samples, Bayley Scales of Infant Development, 3rd edition assessments were performed at age 2 yr. RESULTS: LP Hb levels were increased in PHH infants compared to infants with no ( P  < .0001), low-grade ( P  < .001), and high-grade IVH ( P  < .01). LP ferritin levels were increased in high-grade IVH ( P  < .05) and PHH ( P  < .01) compared to no IVH. There was a significant, positive correlation between LP ferritin and FOHR ( P  < .001, r = 0.45). No group differences were identified for other markers tested. There was a decrease in serial VT Hb and ferritin levels compared to initial measurements (Hb: P  < .05, r = –0.4; ferritin: P  < .05, r = –0.4). FOHR at time of initial VT was correlated with worse age 2 expressive ( P  < .05, r = –0.8) and receptive ( P  < .05, r = –0.8) language performance. VT hepcidin levels were correlated with worse age 2 cognitive performance ( P  < .05, r = –0.8). CONCLUSION: Early elevated LP Hb levels predicted development of PHH, while LP ferritin was elevated in neonates with IVH and PHH. In PHH, higher VT levels of hepcidin, a cellular iron export inhibitor, were associated with worse age 2 cognitive outcomes. These findings implicate Hb and hepcidin as key CSF predictors of PHH and outcome.